Atopic Dermatitis Eczema - Ring, Johannes (Springer International Publishing : Imprint: Springer, 2016)
This book presents the state of the art in research into atopic dermatitis, or atopic eczema, and provides numerous effective practical management recommendations that are grounded in the immense clinical experience of the author. A scientific evidence-based approach to the subject is adopted, progressing from clinical symptoms in different disease stages, molecular genetics, and pathophysiology through to treatment and prevention. All aspects of patient management are covered, including diagnostics, avoidance strategies, emollient therapy, and acute treatment of eczema and itch. Diverse special therapeutic approaches are discussed, ranging from glucocorticoids, topical calcineurin inhibitors, and antimicrobial therapy through to UV therapy, allergen-specific immunotherapy, systemic immunosuppressive therapy, and emerging options. Environmental influences are considered, and there is a focus on the whole human being, with attention to psychosocial aspects of the disease and the benefit of educational programs such as "eczema schools". Atopic Dermatitis will be invaluable for dermatologists, allergists, pediatricians, and general practitioners and informative for other interested persons and sufferers.  .